Material Origin in Folklore Texts of Predominantly Historical Themes - A. G. Igumnov; E. L. Tikhonova (Научный диалог, 2021)
The article deals with the issues of architectonics of folklore texts of historical content: Russian and Ukrainian historical songs, historical ballads, dooms and epics. The relevance of the study is due to the search for a synchronous typological similarity between folklore texts of different ethnic, generic, genre, and poetic nature. Special attention is paid to three aspects of the organization of the song plot: its compositional layering, the combination of several principles in it; the plot meaning of allomotives, explicating the material principle; their styling. The definitions of the material and spiritual principles are given. The objective existence of typological similarities at the level of the allomotive organization of Russian and Ukrainian texts related to the classical, traditional and stage-by-stage types of creativity in the field of historical song folklore is shown. It is shown that this similarity can be explained by the reflection in the texts of vital, everyday empiricism and can acquire different stylistic incarnations: reduced everyday, ascertaining, idealizing. The question is raised about the reasons for the axiological differences in the Russian and Ukrainian folklore traditions. It is proved that the explication of the material principle can have different meanings in the organization of the song plot: optional, meaningful within a fragment of the text, plot-forming.